Analisis kadungan kursus orientasi pensyarah-pensyarah baru dan kesannya terhadap prestasi kerja - Sharifah Maryam, Binti Wan Hasan (Universiti Malaysia Sarawak, (UNIMAS), 2011)
This study aims to ident(fy on how the contents of orientation course fiJr new lecturers in one of the teacher institute in Sarawak affecting their job performance. The main objective of this study is to identify the training needs analysis for the new lectures and its impact on their job performance. It aims to provide guidance to the related parties in improving the quality of orientation course in the future. This study also aims to examine the effectiveness of orientation course as well as modifications that should be made to help the new lecturers in solving the problems of applying the knowledge learned during orientation course in workplace. The results showed that the existing orientation course have its own advantages and disadvantages. In addition, the similarities and differences for each aspect of the study were successfully being identified As for implications, this study brings awareness to the teacher institute and the human resource practitioners about the importance ofproviding effective training to the workers so that their job performance can be improved.